Parametric dependencies of locked mode thresholds in KSTAR L-mode plasmas. (29th June 2021) - Yang, S.M.; Park, J.-K.; Na, Y.S.; In, Y.; Hahn, H.; Jeon, J.W.; Yoo, J.W.; Ko, W.H.; Lee, K.D.; Lee, J.H.; Lee, J.W.; Hong, S.C.; et al.
Abstract: Resonant error fields with toroidal harmonics n = 1 and n = 2 in otherwise axisymmetric tokamak plasmas can drive disruptive locked modes when their strength exceeds a threshold value. This paper presents the sensitivity of error field threshold in global parameters such as line-averaged density and toroidal magnetic field as well as toroidal harmonics dependence in KSTAR L-mode plasmas. The error field threshold for mode-locking increases along with density up to a roll-over density, which coincides well with the linear ohmic confinement (LOC) to saturated ohmic confinement (SOC) density for the studied KSTAR plasmas. This non-monotonic density correlation of the error field threshold in LOC–SOC can be explained by a modification of existing theoretical scaling in SOC, while plasma rotation can also play an important role in setting the resonant error field threshold.